Protein O-GlcNAcylation in Cardiac Pathologies: Past, Present, Future - Ferron, Marine; Denis, Manon; Persello, Antoine; Rathagirishnan, Raahulan; Lauzier, Benjamin (Frontiers in Endocrinology, 2019)
O-GlcNAcylation is a ubiquitous and reversible post-translational protein modification that has recently gained renewed interest due to the rapid development of analytical tools and new molecules designed to specifically increase the level of protein O-GlcNAcylation. The level of O-GlcNAc modification appears to have either deleterious or beneficial effects, depending on the context (exposure time, pathophysiological context). While high O-GlcNAcylation levels are mostly reported in chronic diseases, the increase in O-GlcNAc level in acute stresses such as during ischemia reperfusion or hemorrhagic shock is reported to be beneficial in vitro, ex vivo, or in vivo. In this context, an increase in O-GlcNAc levels could be a potential new cardioprotective therapy, but the ambivalent effects of protein O-GlcNAcylation augmentation remains as a key problem to be solved prior to their transfer to the clinic. The emergence of new analytical tools has opened new avenues to decipher the mechanisms underlying the beneficial effects associated with an O-GlcNAc level increase. A better understanding of the exact roles of O-GlcNAc on protein function, targeting or stability will help to develop more targeted approaches. The aim of this review is to discuss the mechanisms and potential beneficial impact of O-GlcNAc modulation, and its potential as a new clinical target in cardiology.